(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Introduction: Jelly fish or jellies are the members of the phylum Cnidaria (Coelenterata), consisting of a gelatinous umbrella-shaped bell and trailing tentacles. Sting contains toxic peptide, pbospholipase A and histamine-liberating factor. Jelly fish stinging in Bangladesh is rare. Yet, from a management point of view, this epizoonozis might gain importance given the ever-growing popularity of seaside fishering and tourism. We are presenting a case of jelly fish contact illness in Cox’s Bazar Medical College. Case Report: A 30 year old male patient was stung by a jellyfish while tishering in the Bay of Bengal near Teknaf of Cox’s Bazar District on 3rd June’ 2013. A couple of minutes later urticaria were formed in the contact area accompanied by a bmniug and sore sensation. Within few minutes be developed severe abdominal pain, bodyache and parestbaesia. Immediate decontmninalion was done by patient himself with sea water though ideally it should be with 5% acetic acid. Routine laboratory investigations show no abnormality except non-significant ST elevation in ECG. The patient was managed conservatively with antihistamine, corticosteroids and antibiotics and recovered completely within four days.